Energy and Nutrient Intake and Associated Factors Among Pastoral Children in Southern Ethiopia. Issue 4 (December 2020) - Megersa, Bekele; Haile, Abebe; Kitron, Uriel
Background: A better understanding of nutrient intakes and predicting factors will help in designing more effective programs that address the nutrition requirements of pastoral children. Methods: Dietary diversity score (DDS) and amounts of food items consumed were recorded for 538 children aged 6 to 59 months from August to October 2015. The nutrient contents per 100 grams of foods consumed by children were calculated. Median energy and nutrient intakes of children were calculated and compared with the World Health Organization (WHO) recommended nutrient intakes (RNI). The effects of various factors on the median energy adequacy ratio (EAR) and on nutrient adequacy ratio (NAR) were analyzed using logistic regression. Results: Children had low DDS (2.7) with diets dominated by dairy and cereal preparations. Thus, only a few children received the minimum DDS (11.7%) and minimum acceptable diet (5%). Most of the children had low intakes of energy, vitamins (C, B, A, folic acid), iron, and zinc. Autonomy of mothers in decision-making, nonpastoral incomes, crop cultivation, and keeping diverse livestock species had positive effects on nutrient intakes. Children living in villages closer to markets and those aged 6 to 23 months had better NAR than others. The median EAR was higher for children aged 6 to 23 months, when households possessing more animal species and engaged in crop cultivation compared to others. Conclusion: Study children had lower DDS than WHO standards and intakes of several micronutrients were inadequate. Variables associated with median EAR and NAR point to those in need of improvement.